2018
DOI: 10.1287/opre.2018.1740
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note—Multiproduct Pricing Under the Generalized Extreme Value Models with Homogeneous Price Sensitivity Parameters

Abstract: We consider pricing problems when customers choose according to the generalized extreme value (GEV) models and the products have the same price sensitivity parameter. First, we consider the static pricing problem, where we maximize the expected profit obtained from each customer. We show that the optimal prices of the different products have a constant markup over their unit costs. We provide an explicit formula for the optimal markup in terms of the Lambert-W function. This result holds for any arbitrary GEV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…This was demonstrated for the MNL model (e.g., (Aydin and Ryan, 2000, Hopp and Xu, 2005, Maddah and Bish, 2007, Aydin and Porteus, 2008, Akçay et al, 2010), the NL model (e.g., Aydin and Ryan (2000), Hopp and Xu (2005), Maddah and Bish (2007), Aydin and Porteus (2008), Akçay et al (2010), Gallego and Wang (2014), Huh and Li (2015)), and the paired combinatorial logit (PCL) model (Li and Webster, 2017). Lately Zhang et al (2018) showed that this result actually holds for the entire family of generalized extreme value (GEV) models. This stream of research also includes studies in which pricing decisions are optimized jointly with other decisions such as assortment or scheduling decisions (e.g., Du et al (2016), Jalali et al (2019), Bertsimas et al (2020)).…”
Section: Choice-based Pricingmentioning
confidence: 90%
“…This was demonstrated for the MNL model (e.g., (Aydin and Ryan, 2000, Hopp and Xu, 2005, Maddah and Bish, 2007, Aydin and Porteus, 2008, Akçay et al, 2010), the NL model (e.g., Aydin and Ryan (2000), Hopp and Xu (2005), Maddah and Bish (2007), Aydin and Porteus (2008), Akçay et al (2010), Gallego and Wang (2014), Huh and Li (2015)), and the paired combinatorial logit (PCL) model (Li and Webster, 2017). Lately Zhang et al (2018) showed that this result actually holds for the entire family of generalized extreme value (GEV) models. This stream of research also includes studies in which pricing decisions are optimized jointly with other decisions such as assortment or scheduling decisions (e.g., Du et al (2016), Jalali et al (2019), Bertsimas et al (2020)).…”
Section: Choice-based Pricingmentioning
confidence: 90%
“…Keller et al (2014) discussed similar concavity results under the general attraction demand model (GAM, which also subsumes the MNL model) and showed that constraints such as price bounds and price ladders could be added to the pricing problem as linear constraints in the market shares. Zhang et al (2018) discussed the multi-product pricing problem under the generalized extreme value (GEV) models (which subsumes the NL model). They showed that the problem could be formulated as a convex program with homogeneous price sensitivity parameters.…”
Section: Related Literaturementioning
confidence: 99%
“…Assuming identical price sensitivities for all products, Chen and Jiang (2019) studied the joint assortment and pricing problem under the multilevel NL model with a capacity limit imposed on all products. Zhang et al (2018) showed that the constant markup property at the optimality holds under the generalized extreme value (GEV) models, including the MNL, NL, and PCL models. Despite the effort of these papers, the assumption that all products have the same price sensitivity is apparently not realistic and thus leads to a large gap in the literature that cannot be ignored (Erdem et al, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From another point of view, most of the literature is based on an exact preference function from buying a product associated with characteristics such as price and quality, while the constraint sometimes is too strict to accurately describe real situations. Only two papers considered the general choice probability function: Wang (2012) (based on the MNL model) and Zhang et al (2018) (based on the GEV model). These two studies, however, were also based on the identical price sensitivity assumption.…”
Section: Literature Reviewmentioning
confidence: 99%